The Acceptance Of Breast Self-Examination (BSE) Teleconsultation Using TAM-IDT-TRUST Model - Talib, Norayu Abdul (2012)
Health informatics research has expanded and recently focuses on information systems design and implementation. However, there is still very limited study on how end users react to already implemented system in this domain. Therefore, there is a strong need to develop and gain empirical support for models of technology acceptance which in turn help in improving the information system acceptance and its usage.